Water Quality and Sediment Characteristics of the Batang Baleh, Sarawak - Heng, Teresa Lee Eng (Universiti Malaysia Sarawak(UNIMAS), 2018)
Water is important for living organisms. The increase of human activities along a river affects the water quality and sediment characteristics. This study was conducted to determine the water quality and sediment characteristics of the Batang Baleh and its tributaries and the effect of weather on the water quality. Thirty-four stations were selected along Batang Baleh and its tributaries. Five different trips were carried out from February 2015 to January 2016. One sampling took place at each station in the upstream and midstream areas of Batang Baleh whereas three trips were made to the downstream area. The results of this study show that stations near logging activities had significantly higher levels of water turbidity, TSS, COD, TP, Chl-a, NO2-N, NO3-N, TAN and Org-N, and sediment TP, TKN, OM and TOC. The range of water turbidity, TSS, COD, TP and Chl-a are 476.97 NTU – 1176.70 NTU, 487 mg/L – 1040 mg/L, 102.0 mg/L – 187.6 mg/L, 319 μg/L – 880 μg/L and 0.52 mg/m3 – 1.48 mg/m3 respectively. NO2-N, NO3-N, TAN and Org-N values range from 0.005 mg/L – 0.020 mg/L, 0.013 mg/L – 0.028 mg/L, 0.43 mg/L – 1.28 mg/L and 0.74 mg/L – 1.29 mg/L respectively. Sediment TP, TKN, OM and TOC values range from 110.5 mg/kg – 161.1 mg/kg, 793.8 mg/kg – 931.1 mg/kg, 2.17 % – 4.41 %, 0.85 % – 1.94 % respectively. Stations near longhouses had significantly higher levels of water TP, NO2-N, NO3-N and sediment TKN. The water TP, NO2-N, NO3-N and sediment TKN values ranged from 207 μg/L – 375 μg/L, 0.004 mg/L – 0.019 mg/L, 0.006 mg/L – 0.017 mg/L, 571.0 mg/kg – 895.7 mg/kg respectively. The sediment was not polluted in TP as the values did not exceed the Lowest Effect Limit of the Ontario Sediment Standards. However, nine and twenty-one stations of TOC and TKN respectively exceeded the Lowest Effect Level which means that the sediment may have adverse effect on some benthic organisms. During the wet season (January 2016), high mean values of TSS (542 mg/L) and TP (292 μg/L) reduced the water quality of the downstream area. Based on WQI, eight stations were classified as Clean and one station was Polluted while the rest were Slightly Polluted. Sungai Gaat complied with Class II of WQI and all parameters fall in Class I or Class II of NWQS during high water level. The downstream stations classified as Clean during high water level deteriorated to Slightly Polluted status during low and/or medium water levels due to a decrease in DO value and an increase in BOD and COD values. The practice of selective logging and proper discharge of municipal wastes from local villagers are needed for water quality improvement of this river.